2020
DOI: 10.3389/fonc.2020.00426
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Non-targeted and Targeted Metabolomics Uncovers Amino Acid Markers of Oral Squamous Cell Carcinoma

Abstract: Purpose: It is very important to develop potential molecular associated with oral squamous cell carcinoma (OSCC) malignant transformation and progression. Thus, the aim of our study was to determine the amino acid metabolic characteristics of OSCC patients and test their diagnostic value.Experimental Design: Eight pairs of matched tumor and normal samples were collected for gas chromatography-mass spectrometry (GC-MS) high-throughput untargeted analysis. Another 20 cases (each case including tumor and normal t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 30 publications
3
14
0
Order By: Relevance
“…Moreover, high expression of CA9 and PGAM1 were associated with inferior prognosis in OSCC, which in part strengthened our data (33,35). Noticeably, Yang et al utilized gas chromatography-mass spectrometry highthroughput analysis to determine the amino acid metabolic characteristics of OSCC and found that a panel including three amino acids (glutamate, aspartic acid, and proline) was identified as potential diagnostic biomarkers of OSCC (37). These findings may add further support to the key roles of dysregulated metabolism responsible for OSCC initiation and progression, thus ultimately impacting patient prognosis.…”
supporting
confidence: 85%
“…Moreover, high expression of CA9 and PGAM1 were associated with inferior prognosis in OSCC, which in part strengthened our data (33,35). Noticeably, Yang et al utilized gas chromatography-mass spectrometry highthroughput analysis to determine the amino acid metabolic characteristics of OSCC and found that a panel including three amino acids (glutamate, aspartic acid, and proline) was identified as potential diagnostic biomarkers of OSCC (37). These findings may add further support to the key roles of dysregulated metabolism responsible for OSCC initiation and progression, thus ultimately impacting patient prognosis.…”
supporting
confidence: 85%
“…Although a combination of non-targeted and targeted metabolomics have revealed the aberrant levels of several amino acids from normal epithelium to OSCC, the potential function of dysregulated amino acids metabolism behind OSCC metastasis is still unclear ( 17 ). PNI, as a third route for tumor dissemination besides the local invasion and lymphovascular metastasis, was demonstrated in this study to have correlations with the amino acids metabolism disorder.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to increased glucose and fatty acids metabolism during cancer progression, amino acid metabolism also increases to match demands for cancer cells growth and metastasis ( 16 ). For example, by a combination of non-targeted and targeted metabolomics, a panel including three amino acids ( l -glutamate, l -aspartic acid, and l -proline) was identified as potential diagnostic biomarkers of OSCC ( 17 ). l -tryptophan metabolism promotes tumor invasion, metastasis and dysregulates immune cells infiltration thereby accelerating cancer progression ( 18 , 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…Targeted metabolomics uses reference standards for metabolite identification, making it more sensitive and accurate compared to untargeted metabolomics, thereby allowing absolute quantification of metabolites of interest [ 34 ]. Numerous studies of various cancer types have used both untargeted and targeted metabolomics for the discovery of biomarkers or the evaluation of cancer therapies [ 36 , 37 , 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%